Comparison of batch and in‐line PECVD of a‐Si:H passivation layers for silicon heterojunction solar cells. Issue 10 (5th October 2016) - Landheer, Kees; Kaiser, Monja; Poulios, Ioannis; Dörenkämper, Maarten; Soppe, Wim J.; Schropp, Ruud E. I.; Rath, Jatin K.
Abstract : We present PECVD deposition of i‐a‐Si:H in an in‐line configuration for the fabrication of silicon heterojunction solar cells. For industry, in‐line processing has the potential to increase production throughput and yield. We compared batch and in‐line fabrication of i‐a‐Si:H passivation samples with identical plasma conditions and observed that the a‐Si:H material properties do not significantly differ. In batch‐type production the substrate is in the plasma zone at the moment of ignition, whereas for in‐line deposition the substrate is introduced into the plasma zone when steady plasma conditions have been reached. Our preliminary results show that there are depositions conditions that result both for in‐line and batch‐type deposition in good i‐a‐Si:H passivation layers. Therefore both methods can equally well be considered for the production of silicon heterojunction solar cells. (© 2016 WILEY‐VCH Verlag GmbH &Co. KGaA, Weinheim) Abstract : In‐line as well as batch‐type PECVD reactors can create a‐Si:H passivation layers for silicon heterojunction solar cells. Here the authors show this with a reactor that enables deposition on both moving and stationary substrates. In‐line deposition can be beneficial for production throughput and yield.